In vitro cellular activity of maghemite/cerium oxide magnetic nanoparticles with antioxidant properties - Moskvin, Maksym; Huntošová, Veronika; Herynek, Vít; Matouš, Petr; Michalcová, Alena; Lobaz, Volodymyr; Zasońska, Beata; Šlouf, Miroslav; Seliga, Róbert; Horák, Daniel (Colloids and surfaces. B, Biointerfaces, 2021)
Magnetic γ-Fe2O3/CeO2 nanoparticles were obtained by precipitation of Ce(NO3)3 with ammonia in the presence of γ-Fe2O3 seeds. The formation of CeO2 nanoparticles on the seeds was confirmed by transmission electron microscopy linked with selected area electron diffraction, energy-dispersive X-ray spectroscopy, electron energy loss spectroscopy, and dynamic light scattering. The γ-Fe2O3/CeO2 particle surface was functionalized with PEG-neridronate to improve the colloidal stability in PBS and biocompatibility. Chemical and in vitro biological assays proved that the nanoparticles, due to the presence of cerium oxide, effectively scavenged radicals, thus decreasing oxidative stress in the model cell line. PEG functionalization of the nanoparticles diminished their in vitro aggregation and facilitated lysosomal cargo degradation in cancer cells during autophagy, which resulted in concentration-dependent cytotoxicity of the nanoparticles. Finally, the iron oxide core allowed easy magnetic separation of the particles from liquid media and may enable monitoring of nanoparticle biodistribution in organisms using magnetic resonance imaging.
Keywords: Maghemite; Ferric Compounds; antioxidancia; Cerium oxide; Cerium; Oxidative stress; magnetické nanočástice; nanočástice; cer; Antioxidants; Nanoparticles; tkáňová distribuce; Antioxidant; Tissue Distribution; železité sloučeniny; Magnetite Nanoparticles